Analisis Hasil Belajar Siswa Menggunakan Pembelajaran Berbasis Virtual pada Masa Pandemi Covid-19 di SD Negeri 75 Palembang - Astuti, Astri; Misdalina, Misdalina; Hera, Treny (Indonesian Research Journal on Education, 2022)
This study aims to describe student learning outcomes using virtual-based learning during the Covid-19 pandemic at SD Negrei 75 Palembang. The question to be answered from this research is how are student learning outcomes using virtual-based learning during the covid-19 pandemic? and how difficult is it to use virtual-based learning during the covid-19 pandemic. This study uses qualitative methods, the informants of this research are the principals, and teachers of class V A. The data collection of this research was carried out through observation, interviews, and documentation. data analysis techniquesused with data reduction, data presentation, and verification. The results of this study are as follows: (1) Student learning outcomes during the covid-19 pandemic have been achieved (2) In implementing virtualbased learning, the difficulties experienced by students are such as the absence of internet quota and there are also some students who do not have mobile phones, while the teacher does not experience anydifficulties in carrying out learning, because before the teaching and learning process students always prepare everything needed during learning such as books, pencils, cellphones or laptops. Meanwhile, the teacher also prepares lesson plans, teaching materials and learning media in the form of videos that have been made to master the learning materials that will be given to students perfectly.